PENERAPAN MODEL EVALUASI CIPP DALAM MENGEVALUASI PROGRAM LAYANAN PAUD HOLISTIK INTEGRATIF - Petrus Redy Partus Jaya; Felisitas Ndeot (PERNIK : Jurnal Pendidikan Anak Usia Dini, 2018)
Abstract: This paper aims at designing the evaluation model CIPP in evaluating holistic integrative program services in early childhood education.A description of the terminology evaluation and evaluation of the program be placed on early so that the reader can see the holistic integrative services in early childhood education as a program.Next, elaborated on the model of evaluation of CIPP. An understanding of the four components of the CIPP evaluation be the key to implementing this model in evaluating program services holistic integrative in early childhood education.In the four components of the CIPP evaluation there are a few key questions: "what is needed?"; "what should I do?"; "is the program implemented?"; and "how the success rate of the program?".Shove off from these major questions, CIPP model can be applied to evaluate service program holistic integrative in early childhood education from the aspect of Context, Input, Process, and Product. The development of the object and questions of the evaluation refers to the Regulation of the President of the Republic of Indonesia Number 60 of 2013 and Technical Guidelines for the Implementation of Early Childhood Education (PAUD) at the PAUD Unit level. Keywords: evaluation program, PAUD HI,CIPP evaluation model  Abstrak :Tulisan ini bertujuan merancang model evaluasi CIPP dalam mengevaluasi program layanan PAUD HI ditingkat satuan PAUD. Uraian tentang terminologi evaluasi dan evaluasi program ditempatkan pada awal tulisan agar pembaca dapat melihat layanan PAUD HI sebagai suatu program. Selanjutnya, diuraikan tentang model evaluasi CIPP. Pemahaman tentang empat komponen evaluasi CIPP menjadi kunci untuk menerapkan model ini dalam mengevaluasi program layanan PAUD HI.  Dalam empat komponen evaluasi CIPP terdapat beberapa pertanyaan kunci, yaitu “apa yang dibutuhkan?”; “apa yang harus dilakukan?”; “apakah program dilaksanakan?”; dan “bagaimana tingkat keberhasilan program?”. Bertolak dari beberapa pertanyaan utama ini, model CIPP dapat diterapkan untuk mengevaluasi program layanan PAUD HI dari aspek Context, Input, Process, dan Product. Pengembangan objek dan pertanyaan evaluasi mengacu pada Peraturan Presiden Republik Indonesia Nomor 60 tahun 2013 dan Petunjuk Teknis Penyelenggaraan PAUD HI di tingkat Satuan PAUD. Kata Kunci: evaluasi, program, PAUD HI, model evaluasi CIPP